On Topological Properties of Degree-Based Entropy of Hex-Derived Network of Type 3. (4th May 2022) - Zhu, Cun-Bin; Ali, Haidar; Ali, Bilal; Ali, Parvez; Liu, Jia-Bao
Abstract : Hex-derived network has an assortment of significant applications in medicine store, equipment, and network organization. Graph entropy depends upon distribution probability of vertex set and on graph itself. There are numerous issues in discrete math, software engineering, statistics, and data innovation where graph entropies are utilized to portray the reasonable constructions. In this paper, we talk about hex-derived network of type 3 denoted as HDN 3 n . We likewise figure degree-based entropies, for example, Randic', ABC, and GA entropy of HDN 3 n .